An innovative, non-invasive sensation meter allows for a more comprehensive understanding of bladder sensation events: A prospective study in participants with normal bladder function - Naimi, Hameeda A. (Neurourol Urodyn, 2018)
AIMS: There is currently no standardized method of characterizing changes in bladder sensation during bladder filling outside of the urodynamics laboratory. The purpose of this investigation was to characterize real-time bladder sensation events using a sensation meter during oral hydration in individuals with normal bladder function. METHODS: Participants enrolled in an accelerated hydration study drank 2 L Gatorade-G2® and utilized a sensation meter to record real-time bladder sensation (0–100%), verbal sensory thresholds, and sensation descriptors of “tense,” “pressure,” “tingling,” “painful,” and “other” for two consecutive fill-void cycles. RESULTS: Data from 21 participants (12 females/9 males) were obtained and demonstrated an average of 8–9 sensation events (significant changes in sensation) per fill with no differences in the total number of sensation events and volume between sensation events (fill 1 vs fill 2). An increased number of sensation events occurred at higher capacity quartiles. Event descriptors of “pressure” and “tingling” were the most commonly chosen descriptors in both fills. CONCLUSIONS: The innovative sensation meter includes the sensation event descriptors of “tense,” “tingling,” “pressure,” and “painful,” to enable a more comprehensive understanding of bladder sensation as well as real-time identification, quantification, and characterization of sensation events. The study demonstrates 8–9 events per fill, acceleration of sensation during filling, and unique sensation event descriptor patterns. This technology may be helpful in the identification of novel sensation patterns associated with overactive bladder (OAB) and aging.